A Wild-plant extract could eliminate infectious-pathogens, Ranyah, KSA - Mostafa M. Sabra, Sherifa (Journal of Biotechnology and Biomedical Science, 2023)
Saudi Arabia is rich in Juniperusprocera Hochst. ex Endl (Cupressaceae) as a medicinal plant. Its known as Arar, its present southwards, KSA. It's used as traditional medicine in the southwestern, KSA. The aim was according to "Saudi Arabian Customs" in using wild-plant extract for treatment and prevention of infectious-pathogens. That was to use Juniperusprocerafrom Ranyah, KSA to eliminate infectious-pathogens that were isolated from patients in the same area. This was the use may reduce the use of chemicals, as well it may be an alternative to chemotherapy. Practice included preparation of wild-plant extract, preparation of infectious-pathogens, interaction to wild-plant extract, and direct total cell count by "Bread Test". Juniperusprocera one crude concentration killed all infectious-pathogens during one day. Lower Juniperusprocera crude extract concentrations eliminated infectious-pathogens within more than one day. The mean number of dead sells / mL of Staphylococcus sp., Streptococcus sp, and Streptococcus pyogenes were (84.9 / mL, 87.0 / mL, and 77.8 / mL). The mean percent of dead cells were (80.0%, 82.0%, and 73.4%). The meannumber of dead sells / mL of Salmonella sp., Shigella sp, and Escherichia coli were (72.6 / mL, 76.1 / mL, and 79.0 / mL). The mean percent of dead cells were (68.5%, 71.8%, and 74.5%). The mean number of Candida albicans dead sells / mL was 69.3 / mL, the mean percent of dead cells was 65.4%. It was concluded that found from the results, the Juniperusprocera extract was preferred "Saudi Arabian Customs" to be used in three quarter and one crude concentration, as the infectious-pathogens eliminating within one day. It was recommended that the Juniperusprocera extract will be used for herbal treatment according to "Saudi Arabian Customs". That will be remark and follow-up through the "Official Herbal Treatment Dept.". That will appropriate the doses will estimate for each patient to eliminate and protect against the infectious-pathogens.
Keywords: Juniperus procera; Staphylococcus sp.; Streptococcus sp; Streptococcus pyogenes; Salmonella sp.; Shigella sp; Escherichia coli; Candida albicans